Integrating maxillary dentition and 3D facial photo using a modified CAD/CAM facebow - Peiqi Wang; Hui Xu; Rui Gu; Liwei Zhu; Ding Bai; Chaoran Xue (BMC, 2022)
Abstract Background Accurate integration of the dentitions with the face is essential in dental clinical practice. Here we introduce a noninvasive and efficient protocol to integrate the digitized maxillary dentition with the three-dimensional (3D) facial photo using a prefabricated modified computer-aided design/computer-aided manufacture (CAD/CAM) facebow. Methods To integrate the maxillary dentition with the 3D facial photo, the CAD/CAM facebow protocol was applied to 20 patients by taking a series of 3D facial photos in the clinic and integrating them in the laboratory. The integration accuracy of this protocol was compared with that of a valid 3D computed tomography (CT)-aided protocol concerning translational deviations of the landmarks representing maxillary incisors and maxillary first molars as well as the rotational deviation of the maxillary dentition. The intra- and inter-observer reproducibility was assessed, and the time of clinical operation and laboratory integration was recorded. Results This facebow-aided protocol generated 3D fused images with colored faces and high-resolution dentitions, and showed high reproducibility. Compared with the well-established CT-aided protocol, the translational deviations ranged from 0 to 1.196 mm, with mean values ranging from 0.134 to 0.444 mm, and a relatively high integration error was found in the vertical dimension (Z) with a mean ± standard deviation (SD) of 0.379 ± 0.282 mm. Meanwhile, the rotational deviations ranged from 0.020 to 0.930°, with mean values less than 1°, and the most evident deviation was seen in pitch rotation with a mean ± SD of 0.445 ± 0.262°. The workflow took 4.34 ± 0.19 min (mins) for clinical operation and 11.23 ± 0.29 min for laboratory integration. Conclusion The present radiation-free protocol with the modified CAD/CAM facebow provided accurate and reproducible transfer of the digitized maxillary dentition to the 3D facial photo with high efficiency.